2021
DOI: 10.1111/bjep.12467
|View full text |Cite
|
Sign up to set email alerts
|

Teachers use of fear appeals: Association with student and teacher mental health

Abstract: Background Fear appeals are discourses commonly used by teachers to motivate students especially when academic outcomes are paramount. Fear appeals have been associated with better and worse academic performance by the student recipients, with some evidence that fear appeals are detrimental for students who are anxious and have lower self‐efficacy. Little is known about the factors that drive teachers’ use of fear appeals beyond a desire to increase motivation to excel. Aims This study examined the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…In this sense, it could be that, for teachers that rely less-frequently on these kind of messages, when they do so and rely on loss-controlled messages such as "If you don't study, you'll make your parents feel angry" could be interpreted by students as a sense of concern from the teacher towards them, as there are not used to such messages, and thus, making them think their teacher really desires the best for them (Connell & Wellborn, 1991;Taylor & Ntoumanis, 2007). Contrastingly, when loss-framed messages are accompanied by an autonomous motivational appeal, relying on messages such as "If you don't pay attention, you won't study what you want" even with a low frequency might instead be interpreted by students' as an attack towards them, as a critic or intrusion (MacGeorge et al, 2008) and, thus, in line with previous studies (Belcher et al, 2021;Putwain & Remedios, 2014), negatively predicting TS-relatedness.…”
Section: Student Levelsupporting
confidence: 75%
See 2 more Smart Citations
“…In this sense, it could be that, for teachers that rely less-frequently on these kind of messages, when they do so and rely on loss-controlled messages such as "If you don't study, you'll make your parents feel angry" could be interpreted by students as a sense of concern from the teacher towards them, as there are not used to such messages, and thus, making them think their teacher really desires the best for them (Connell & Wellborn, 1991;Taylor & Ntoumanis, 2007). Contrastingly, when loss-framed messages are accompanied by an autonomous motivational appeal, relying on messages such as "If you don't pay attention, you won't study what you want" even with a low frequency might instead be interpreted by students' as an attack towards them, as a critic or intrusion (MacGeorge et al, 2008) and, thus, in line with previous studies (Belcher et al, 2021;Putwain & Remedios, 2014), negatively predicting TS-relatedness.…”
Section: Student Levelsupporting
confidence: 75%
“…Such studies have focused mainly on exploring loss-framed messages, providing evidence on the negative impact these can have on student. Specifically, they have been commonly related to students' negative emotions such as anxiety, distress, worry, and hopelessness following avoidance behaviours such as disengagement, strategic withdrawal of effort, and procrastination (Belcher et al, 2021;Nicholson et al, 2019;Putwain & Remedios, 2014;Putwain et al, 2017Putwain et al, , 2019Putwain et al, , 2021. Contrastingly, the impact of gain-framed messages remains largely understudied, with only a few studies examining such messages in relation with student's learning outcomes (Santana-Monagas et al, 2022a, b; that do not examine the influence of gain-framed messages on students' well-being.…”
Section: Teacher's Engaging Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that autonomy and academic development are related to the self-determination of the individual and the process of its development (Famero, 2021). Research during COVID shows that teachers' appeal to fear as a way to increase motivation and improve performance is a failure (Belcher et al, 2022). At the same time, the lack of direct contact with the teacher in long online learning sessions reduces academic performance on average (Norris and Fenwick, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today, the most common stressor is the COVID-19 pandemic and measures introduced to by governments to tackle its consequences and prevent further spread (Belcher et al, 2022;Norris and Fenwick, 2022). Researchers all over the globe found that these quarantine measures had a negative effect on schooling, which manifested in heightened anxiety, insecurity, and increased time spent on social media or playing video games (Hertz and Barrios, 2021;Paschke et al, 2021).…”
Section: Introductionmentioning
confidence: 99%